2012
DOI: 10.1016/j.cub.2012.10.009
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic Engineering Unveils the Function of Genital Morphology

Abstract: The rapidly evolving and often extraordinarily complex appearance of male genital morphology of internally fertilizing animals has been recognized for centuries. Postcopulatory sexual selection is regarded as the likely evolutionary engine of this diversity, but direct support for this hypothesis is limited. We used two complementary approaches, evolution through artificial selection and microscale laser surgery, to experimentally manipulate genital morphology in an insect model system. We then assessed the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
173
3
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(182 citation statements)
references
References 31 publications
5
173
3
1
Order By: Relevance
“…Our study joins a very few 'phenotypic engineering' studies of genitalia [6,7,[10][11][12][13][14][15]. These studies have alternately supported a pre-and/or post-copulatory function of the manipulated structures.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our study joins a very few 'phenotypic engineering' studies of genitalia [6,7,[10][11][12][13][14][15]. These studies have alternately supported a pre-and/or post-copulatory function of the manipulated structures.…”
Section: Discussionmentioning
confidence: 99%
“…Although most of the evidence we have for the role of sexual selection in genital evolution tends to be correlative [3], a few recent studies provide more direct evidence from the experimental evolution of genitalia [8][9][10] or phenotypic manipulations of genital features [6,7,[10][11][12][13][14][15]. These latter 'phenotypic engineering' studies are particularly informative, because they focus directly on function and offer the promise of finely distinguishing among alternative mechanisms of selection, unimpeded by unmeasured correlated traits.…”
Section: Introductionmentioning
confidence: 99%
“…Recently the competitive fertilization success of male's ejaculate, whose aedeagal spine length was manipulated by micro-scale laser surgery, was assessed by using high-resolution radioisotopic labelling. Male with longer species-specific sclerotized genital spines on aedeagus were more successful in gaining fertilization (Hotzy et al 2012). The importance of male driven copulatory mechanics and strategies has been revealed in the rapid diversification of genitalia of Drosophila flies (Jagadeeshan & Singh 2006).…”
Section: Accelerated Reproductive Isolationmentioning
confidence: 99%
“…Creating males and females with different genital genotypes using experimental evolution can reveal coevolutionary processes underlying genital traits. A recent experiment in seed beetles Callosobruchus maculatus generated phenotypic variation via both artificial selection and experimental ablation of spines and elegantly showed that longer spines, are beneficial to male fitness (Hotzy et al 2012). Similarly, a recent study in Drosophila generated variation in male genitalia by creating introgressed lines between D. mauritiana and D. sechelia.…”
Section: Distinguishing Between Mechanisms Of Genital Coevolutionmentioning
confidence: 99%